Single Frontal Burr-Hole Craniostomy Under Local Anesthesia for Treating Chronic Subdural Hematoma in the Septuagenarians and Older Adults: Surgical Technique and Results - Adeleye, Amos Olufemi; Ulasi, Bartholomew I. (Indian Journal of Neurotrauma, 2023)
Background Chronic subdural hematoma (CSDH) is not a totally benign disease in the elderly patients, especially those aged 70 years and above. Hence, the surgical treatment of CSDH in aged patients needs to be as minimally disruptive as possible.Methods An annotated description of the surgical technique of single frontal burr-hole craniostomy performed under local anesthesia and without closed tube drainage for evacuating CSDH in the septuagenarians and older adults is given. We also review the outcome of the procedure on a prospective consecutive cohort of patients in our serviceResults Thirty patients, 25 males, aged 70 years and above successfully underwent this surgical procedure. Their mean age was 76.5 years (standard deviation, 4.3). The CSDH was bilateral in 30% (9/30), and more left sided in the rest, the unilateral cases, and was of mixed density radiologically, in most cases (73%, 22/30). Clinical presentation was mainly gait impairment, cognitive decline, and headache, and 57% (17/30) presented with coma or stupor as assessed by the Markwalder grading scale.The surgery was successfully executed in all, median duration 45.0 minutes (interquartile range 37.3–60.0), and solely under local anesthesia in 77% (23/30) or with momentary short-acting sedation in the rest. The outcome was very good in 90.0% (27/30) using the modified Rankin Scale (mRS) including two-third (20/30) completely asymptomatic (mRS 0) and 7/30 with only slight symptoms/disability, mRS ≤ 2. Three patients died perioperatively, all presenting in coma.Conclusion This surgical technique appears very effectual for CSDH, is executed at a comparatively low cost, and, being much less disruptive than other traditional methods, may be a more homeostatic operative treatment in geriatric patients at least.
Keywords: chronic subdural hematoma; burr-hole craniostomy; single frontal burr-hole; local anesthesia; geriatric patients